Regulation of translation elongation and integrated stress response in heat-shocked neurons - Caitlin M. Seluzicki; Milad Razavi-Mohseni; Fulya Türker; Priyal Patel; Boyang Hua; Michael A. Beer; Loyal Goff; Seth S. Margolis (Cell Reports)
Summary: Neurons deviate from a canonical heat shock response (HSR). Here, we revealed that neuronal adaptation to heat shock accompanies a brake on mRNA translation, slowed elongating ribosomes, phosphorylation of eukaryotic elongation factor-2 (p-eEF2), and suppressed the integrated stress response (ISR). Returning neurons to control temperature within 1 h of starting heat shock was necessary for survival and allowed for restored translation following dephosphorylation of eEF2. Subsequent to recovery, neurons briefly activated the ISR and were sensitive to the ISR inhibitor ISRIB, which enhanced protein synthesis and survival. Ribosome profiling and RNA sequencing (RNA-seq) identified newly synthesized and existing transcripts associated with ribosomes during heat shock. Preservation of these transcripts for translation during recovery was in part mediated by p-eEF2 and slowed ribosomes. Our work supports a neuronal heat shock model of a partially suspended state of translation poised for rapid reversal if recovery becomes an option and provides insight into regulation between the HSR and the ISR.